2018
DOI: 10.17116/hirurgia2018691-100
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of collagen biomaterial local application in complex treatment of the diabetic foot syndrome (final results of the multicenter randomised study)

Abstract: We have proved the efficacy and safety of collagen biomaterial topical application in a diabetic foot syndrome treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Seven studies 24,[38][39][40][41]43,45 reported on absolute wound healing at time frames ranging from 28 days 43 to 24 weeks. 39 Only two 39,41 reported statistically significant improvements in absolute wound healing with use of collagen dressings compared to a control dressing, but both studies were small (<70 participants), lacked details on baseline ulcer and participant characteristics and other aspects of usual care; thus, any positive findings should be interpreted with caution.…”
Section: Outcome: Complete Wound Healingmentioning
confidence: 99%
“…Seven studies 24,[38][39][40][41]43,45 reported on absolute wound healing at time frames ranging from 28 days 43 to 24 weeks. 39 Only two 39,41 reported statistically significant improvements in absolute wound healing with use of collagen dressings compared to a control dressing, but both studies were small (<70 participants), lacked details on baseline ulcer and participant characteristics and other aspects of usual care; thus, any positive findings should be interpreted with caution.…”
Section: Outcome: Complete Wound Healingmentioning
confidence: 99%
“…Four studies compared collagen only with moist wound therapy, 45,47,48,52 one study 46 used collagen-alginate, one used a calcium alginate, 51 one compared a collagen/oxidised regenerated cellulose/silver treatment with foam, 29 one the same collagen/oxidised regenerated cellulose but without silver, 54 one compared collagen with negative pressure wound therapy, 50 one compared collagen with gauze or hydrocolloid dressings 49 , and another two 51,53 alginate alone as the intervention. Of the 12 studies, nine of them 29,[45][46][47]49,[51][52][53][54] did not report a difference in wound healing or reduction in ulcer area at the end of study duration. Thus, any reported positive outcomes should be treated with caution.…”
Section: Honey or Bee Productsmentioning
confidence: 99%
“…Presently, one of the new approaches to the periodontal tissue regeneration is the application of a bioplastic collagen material Collost as a barrier matrix [20]. The gel form of Collost biomaterial is widely used in general surgical practice in the management of chronic wound skin defects of various etiology [21][22][23]. Application of the collagen Collost gel for gum recession treatment, especially as a scaffold in tissue-engineered constructs is considered as a promising technique.…”
Section: Experimental Investigationsmentioning
confidence: 99%